2009
DOI: 10.1002/clc.20558
|View full text |Cite
|
Sign up to set email alerts
|

Wall Motion Abnormalities with Low‐Dose Dobutamine Predict a High Risk of Cardiac Death in Medically Treated Patients with Ischemic Cardiomyopathy

Abstract: Background Severe and extensive coronary artery disease is the underlying cause of stress‐induced wall motion abnormalities (SWMA) with low‐dose (10 µg/kg/min) dobutamine suggesting that these abnormalities may identify those with poor outcome. Hypothesis We assessed the prognostic value of low‐dose SWMA in medically treated patients with ischemic cardiomyopathy. Methods Low‐ and peak‐dose dobutamine echocardiography was performed in 235 patients with ischemic cardiomyopathy (ejection fraction 31% ± 8%) who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These segments are partially viable, have severely reduced perfusion reserve, and are associated with severe, multivessel coronary artery obstruction, reduced collateral supply, and increased cardiac mortality. 51,238 d. Accuracy of DSE for Detection of Viability Numerous studies have shown that low dose or combined low and high dose dobutamine infusion protocols have clinically useful sensitivity (75 to 80%) and specificity (80 to 85%) for identification of viable segments with functional recovery after revascularization. 22,239,240 False-negative exams may occur in hibernating regions with disrupted contractile proteins that cannot respond to dobutamine but eventually manifest functional recovery months after revascularization, with reorganization of contractile proteins.…”
Section: B Dse Protocols For Assessing Viabilitymentioning
confidence: 99%
“…These segments are partially viable, have severely reduced perfusion reserve, and are associated with severe, multivessel coronary artery obstruction, reduced collateral supply, and increased cardiac mortality. 51,238 d. Accuracy of DSE for Detection of Viability Numerous studies have shown that low dose or combined low and high dose dobutamine infusion protocols have clinically useful sensitivity (75 to 80%) and specificity (80 to 85%) for identification of viable segments with functional recovery after revascularization. 22,239,240 False-negative exams may occur in hibernating regions with disrupted contractile proteins that cannot respond to dobutamine but eventually manifest functional recovery months after revascularization, with reorganization of contractile proteins.…”
Section: B Dse Protocols For Assessing Viabilitymentioning
confidence: 99%
“…The sensitivity and specificity of the DSE range vary between 71-97% and 63-95%, respectively (Maskoun et al, 2009).…”
Section: Qanun Medika Volmentioning
confidence: 99%
“…Stress. Several studies have demonstrated the utility of stress echocardiography to identify both resting and poststress systolic wall motion abnormalities [90][91][92]. Additionally, these findings correlate to clinical outcomes.…”
Section: Us Echocardiography Transthoracic Resting Andmentioning
confidence: 99%